Reasons and Barriers for University Students' Leisure-Time Physical Activity: Moderating Effect of Health Education. Issue 6 (December 2019) - Sukys, Saulius; Cesnaitiene, Vida J.; Emeljanovas, Arunas; Mieziene, Brigita; Valantine, Irena; Ossowski, Zbigniew M.
This study aimed to investigate the relationship between health education and motives and barriers for university students' engagement in leisure-time physical activity (PA). The research sample included 709 students (312 females and 397 males) in different years of study, ranging in age between 18-25 years. A questionnaire survey method revealed a significant positive relationship between fitness and health motives and students' leisure-time PA. External barriers were negative predictors of students' leisure-time PA, while more health education-related courses per week were positively associated with students' leisure-time PA. Finally, we found that the number of health education-related courses per week moderated the relationship between fitness and health motives and students' leisure-time PA. These findings suggest that university students' fitness and health motives and external barriers to be physically active outweigh other motives and barriers in determining their leisure-time PA. In addition, health education in university studies can effectively increase students' health-related motivation for PA.